2021
DOI: 10.3390/polym13213620
|View full text |Cite
|
Sign up to set email alerts
|

Physical, Mechanical, and Morphological Properties of Treated Sugar Palm/Glass Reinforced Poly(Lactic Acid) Hybrid Composites

Abstract: This research was performed to evaluate the physical, mechanical, and morphological properties of treated sugar palm fiber (SPF)/glass fiber (GF) reinforced poly(lactic acid) (PLA) hybrid composites. Morphological investigations of tensile and flexural fractured samples of composites were conducted with the help of scanning electron microscopy (SEM). Alkaline and benzoyl chloride (BC) treatments of SPFs were performed. A constant weight fraction of 30% total fiber loading and 70% poly(lactic acid) were conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 74 publications
(120 reference statements)
1
6
0
Order By: Relevance
“…% WF/resin recording the highest Young's modulus at 323.8 MPa [51]. Similar increment in tensile modulus of composite was found by Sherwani et al [52] in which untreated sugar palm fiber/glass fiber-reinforced PLA hybrid composite tensile modulus increased with the addition of GF [52]. Table 4 displays the elongation at break as a function of MF content.…”
supporting
confidence: 78%
“…% WF/resin recording the highest Young's modulus at 323.8 MPa [51]. Similar increment in tensile modulus of composite was found by Sherwani et al [52] in which untreated sugar palm fiber/glass fiber-reinforced PLA hybrid composite tensile modulus increased with the addition of GF [52]. Table 4 displays the elongation at break as a function of MF content.…”
supporting
confidence: 78%
“…Natural fibers such as hemp [3][4][5], pineapple leaf [6,7], flax [8], oil palm [9], and sugar palm [10,11] have been used in composite manufacturing. Moreover, natural fibers in a woven form such as bamboo [12,13], jute [14,15], kenaf [16,17], and banana [18] also have been extensively used in composite fabrication.…”
Section: Introductionmentioning
confidence: 99%
“…After fibre treatment, the percentage of lignin decreased from 33.24 to 0.06%. 69 A previous study had reported that reduced lignin percentage in the fibre enhances char formation, while increased char formation during the burning process is a good indication of flame retardancy. 70 During the burning process, SPF tends to rush into the char phase.…”
Section: Resultsmentioning
confidence: 98%